Implicit and explicit attitudes: an examination of the efficacy of anti-sugar public health campaigns - Kaplan, Michael (School of Management Studies, 2023)
The current obesity epidemic is prevalent, and its potential growth is concerning. Moreover, obesity-inducing food products have become more accessible to consumers, with increases in sugar-sweetened beverage (SSB) consumption necessitating SSB-related taxation. The purpose of this study is to examine whether social-marketing efforts, in the form of an anti-sugar public health campaign (PHC), influence consumer attitudes toward SSBs. In this context, one's self-reported attitude (ie, conscious, explicit attitude) may not accurately reflect one's ‘true' attitude (ie, subconscious, implicit attitude). Therefore, the focus of this study concerns consumers' explicit and implicit attitudes toward SSBs. There are three core objectives of this study: to determine whether anti-sugar PHCs influence consumers' (1) explicit and (2) implicit attitudes toward SSBs, and (3) to determine whether changes in explicit attitudes mediate changes in implicit attitudes, and vice-versa. To examine the efficacy of an anti-sugar PHC, this quantitative and causal research adopts a pre- and post-test control group design. Prior to, and following exposure to an anti-sugar PHC, young adult consumers' explicit attitudes were assessed through self-report surveys, and their implicit attitudes assessed using neuromarketing-based evaluative priming tasks (EPTs). Data were analysed using a combination of paired sample t-tests and structural equation modelling (SEM). This study provides evidence that anti-sugar PHCs influence consumers' explicit and implicit attitudes toward SSBs, and that changes in explicit attitudes mediate changes in implicit attitudes, and vice-versa. Specifically, following exposure to the anti-sugar PHC, less favourable explicit and implicit attitudes toward SSBs demonstrates the usefulness of considering explicit and implicit attitudes when designing and implementing PHCs. The study contributes to the Associative-Propositional Evaluation (APE) model, through the lens of dual-process theory (DPT), by bridging the gap between PHC research and implicit consumer cognition. This study contributes to practice by advocating for marketers' application of neuromarketing techniques in evaluating campaign effectiveness, such as implicit attitudinal measures. Further, this study contributes to policymaker practices by highlighting the effectiveness of anti-sugar PHCs as a supplementary or complementary tool in addressing the obesity epidemic and enhancing societal wellbeing and health.